Enhanced fresh and hardened properties of foamed concrete modified with nano-silica - Md Azree Othuman Mydin; P. Jagadesh; Alireza Bahrami; Anmar Dulaimi; Yasin Onuralp Özkılıç; Roshartini Omar (Heliyon, 2024)
Nowadays, the application of nanotechnology has gained increased attention in the concrete technology field. Several applications of concrete require light weight; one such concrete used is foamed concrete (FC), which has more voids in the microstructure. In this study, nano-silica (NS) was utilized, which exhibits a pozzolanic nature, and it reacts with other pozzolanic compositions (like lime, alumina, etc.) to form hydrated compounds in concrete. Apart from these hydrated compounds, NS acts as a filler material and enhances properties of concrete such as the fresh and hardened properties. This research examines the fresh, hardened, and microstructural properties of FC blended with NS. The ratio of binder and filler used in this research is 1:1.5, with a water-to-binder ratio of 0.45 and a density of 880 kg/m3. A total of six different weight fractions of NS were added to FC mixes, namely 0%, 1%, 2%, 3%, 4%, and 5%. Properties assessed for FC blended with NS were the slump, bulk density, strength parameters (flexural, splitting tensile, and compressive strengths), morphological analysis, water absorption, and porosity. It was concluded from this study that the optimum NS utilized to improve the properties was 3%. Apart from this, the relationship between the mechanical properties and NS dosages was developed. The correlations between the compressive strength and other properties were analyzed, and relationships were developed based on the best statistical approach. This study helps academicians, researchers, and industrialists enhance the properties of FC blended with NS and their relationships to predict concrete properties from other properties.